Microstructure of Aluminium Alloys Casting Intended for Cyclical Thermal Stress - Nova, Iva; Machuta, Jiri (Manufacturing Technology Journal, 2016)
The article presents the microstructure and mechanical properties of aluminium cylinder head engine. The cylinder heads are manufactured by gravity casting. Gravity casting (GC) is very good process for making complex mechanical parts of light metal like aluminium alloys. However recently another light metal has come to the forefront in the quest for fighter vehicles and improved fuel economy. The most commonly used aluminium alloy for gravity casting automotive components is the Al-Si-Mg type. AlSi10Mg is a good purity of aluminium alloy with good corrosion resistance, very good mechanical properties and good castability. AlSi10Mg alloy is slightly hypoeutectic with a low content of accompanying elements and impurities. Exhibits excellent casting and technological properties (good machinability and corrosion resistance). During solidification of this alloy is formed a shrinkage, which is necessary to eliminate by risering. This alloy has a wide foundry application, it is used for gravity casting into metal moulds for production of cylinder heads. This alloy is used for precipitation hardening intermediate Mg2Si phase. It was cast a cylinder head of AlSi10MgMn alloy and it was monitored the structure of the casting.
Keywords: aluminium alloy; crystallization; microstructure; cylinder head engine